1989
DOI: 10.1891/0886-6708.4.2.101
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Child Abuse and Neglect: Review of the Literature and Presentation of Data

Abstract: This report assesses current knowledge about the ecological determinants of child maltreatment and presents data from an aggregate study of co-variation between seven community characteristics and maltreatment rates. A review of these findings revealed literature in the early stages of development. Nothing is known about the ecology of sexual abuse, and studies of physical abuse and neglect have done little more than demonstrate co-variation between reported incidence and neighborhood population and housing ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(85 citation statements)
references
References 0 publications
5
78
0
2
Order By: Relevance
“…9 Several studies have reported associations between economic factors and maltreatment rates at the neighborhood and community levels. [12][13][14][15] Recently, a retrospective study of children admitted to 38 hospitals between 2000 and 2009 showed that rates of admissions for physical abuse and high-risk traumatic brain injury were significantly related to increases in local mortgage foreclosure and delinquency rates in the associated metropolitan areas. 16 Although there is considerable evidence that income inequality has a negative impact on health and wellbeing for both adults and children, and that poverty is associated with rates of child maltreatment, no study has examined the association of income inequality with child maltreatment.…”
mentioning
confidence: 99%
“…9 Several studies have reported associations between economic factors and maltreatment rates at the neighborhood and community levels. [12][13][14][15] Recently, a retrospective study of children admitted to 38 hospitals between 2000 and 2009 showed that rates of admissions for physical abuse and high-risk traumatic brain injury were significantly related to increases in local mortgage foreclosure and delinquency rates in the associated metropolitan areas. 16 Although there is considerable evidence that income inequality has a negative impact on health and wellbeing for both adults and children, and that poverty is associated with rates of child maltreatment, no study has examined the association of income inequality with child maltreatment.…”
mentioning
confidence: 99%
“…Les recherches de Coulton et ses collègues (1995; montrent que le niveau de pauvreté du quartier, le fardeau de garde et l'instabilité économique et résidentielle peuvent expli-quer, en partie, la variance des taux de mauvais traitements observés dans les communautés. Le nomadisme territorial comme facteur associé à la négligence parentale est aussi mis en évidence par les recherches de Zuravin (1989) ainsi que de Bouchard, LeBossé et Dumont (1995).…”
Section: Facteurs Susceptibles D'influencer Le Bien-être Des Famillesunclassified
“…The relationship between rates of child maltreatment and different neighborhood characteristics, such as social impoverishment, poverty, demographic composition, and deviant behavior, has been well established (e.g., Bouchard, 1987;Coulton, Korbin, & Su, 1999;Coulton, Korbin, Su, & Chow, 1995;Drake & Pandey, 1996;Garbarino & Sherman, 1980;Nelson & Baldwin, 2002;Vinson, Baldry, & Hargreaves, 1996;Zuravin, 1989). However, the way in which these neighborhood characteristics influence rates of child maltreatment still remains a matter not fully understood that deserves further research attention (Coulton et al, 1999;Gracia & Musitu, 2003;Korbin, 2003).…”
Section: Introductionmentioning
confidence: 99%